II Encounter on natural resources Pearl Lagoon Basin. "An activity framed by the initiative of institutionalization of the communal organizations of the basin and neighboring municipalities addressed to achieving a shared administration of the natural resources" / Secretary's office for natural Resources - Simons, Bertha (1997)
Antecedent to the official encounter, dvelopment and results of the work day, making up of the teams, contribution of the groups, development and results, agreements on the second encounter on the natural resources of The Pearl Lagoon basin, delcaration second encounter of natural resouces pearl Lagoon basin RAAS, covenant of the act of constitution of the committee of natural resources of the pearl lagoon basin